(IM)POSSIBLE LEGACIES OF SPORTS MEGA-EVENTS (Fiep Bulletin - online, 2014)
This study does a bibliographical research regarding the impacts of Sports Mega-events and more precisely the World Cup. The following subjects were approached for theoretical foundation: what are sports mega-events, their legacies and contributions to the host country, as well as economic issues that depict the possible “white elephants”, demands on budget, financing, renovation or construction projects, infrastructure of the surroundings, environmental licensing and others. The initial search occurred on Portal CAPES website, with the keywords: Mega-event, finding 25 articles, Legacy – Mega-event, providing only 4 articles and finally World Cup, when it was made a thorough gathering of 623 articles and a book that were found. Regarding sports mega-events we have worked with a critical and investigative view, thus being able to realize that the legacies so much intoned by all organizations and media related with the Mega-events are, in fact, not always clearly shown, or worse, they do not always actually happen, therefore becoming an inexistent scenario.
Keywords: Sports Mega-event; World Cup; Legacy